PENGARUH TEKNOLOGI KOMPUTER TERHADAP EFEKTIVITAS KERJA PEGAWAI DI KANTOR CAMAT TUJUH BELAS KABUPATEN BENGKAYANG - H. Suseno Dwi Gustomo E.42009044 (FISIP Universitas Tanjungpura Pontianak, 2022)
The Impact of Computer Technology to Employees Performance Effectiveness at District TujuhBelas Office BengkayangRegency.Script. Pontianak: Government Study Program Faculty of Social Politics Tanjungpura University Collaborate with West Kalimantan Province Government.The aim of this script is to investigate and analyze The Impact of Computer Technology to Employees Performance Effectiveness at District TujuhBelas Office Bengkayang Regency. Through simple linear regression statistical tests using the existing population is about 20 people .The results showed that there is a correlation coefficient (R) of 0,849. Based on statistical data analysis, the indicators in this study is valid and reliable. Hypothesis testing shows that there are significant Computer Technologies for 72.1% of The Effectiveness of Employees Working at The District Office Gorged Tujuh Belas Districts while the remaining 27.9% influenced by other factors. This means that Computer Technology Affect The Effectiveness of Employees Working at District Tujuh Belas OfficeBengkayang Regency. Keywords : Computer Technology, Performance Effectiveness